Providing informal home care for pressure ulcer patients: how it affects carers' quality of life and burden. Issue 19 (31st August 2016) - Rodrigues, Alexandre M.; Ferreira, Pedro L.; Ferré‐Grau, Carmen
Abstract : Aims and objectives: To evaluate the quality of life of informal caregivers of patients with pressure ulcer; to assess their levels of burden; to analyse the variables influencing both their quality of life and burden. Background: Informal caregivers of pressure ulcer patients, besides coping with the natural dependency of these patients, deal with the specificity of caring these types of wounds. This situation has an impact on not only the quality of life and burden felt by informal caregivers but also on individual and familiar dynamics. Design: Descriptive and correlational study. Methods: This study focused on 145 informal caregivers providing home care. Measurement instruments were: SF‐36v2 and the Burden Interview Scale. Descriptive analysis of the quantitative variables was carried out according to measures of central tendency, and the qualitative variables were described using absolute and relative frequencies. The relationships or associations between variables were explored through correlational analysis and, whenever the data allowed, multivariate techniques were used. Results and discussion: Informal caregivers showed low levels of quality of life and, most of them, significant burden. Quality of life decreased with overload, with the increasing number of pressure ulcer and with less experience of informal caregivers, with lack of financial remuneration, with unemployment, with patient positioning and with the direct care of the wound. The burden increased with the number of pressure ulcer in each patient and with the lack of financial remuneration. Conclusion: These informal caregivers have low quality of life and are overburdened. Both situations are positively and negatively influenced by factors related to the pressure ulcer and to the patients' sociodemographic data. Relevance to clinical practice: The results of this study allow more effective monitoring by health professionals of levels of burden and quality of life encountered in pressure ulcer informal caregivers, as well as direct interventions to inhibit the factors inducing burden and enhance those that improve quality of life.